2018
DOI: 10.1002/dvg.23259
|View full text |Cite
|
Sign up to set email alerts
|

Using human sequencing to guide craniofacial research

Abstract: Summary A recent convergence of technological innovations has re‐energized the ability to apply genetics to research in human craniofacial development. Next‐generation exome and whole genome sequencing have significantly dropped in price, making it relatively trivial to sequence and analyze patients and families with congenital craniofacial anomalies. A concurrent revolution in genome editing with the use of the CRISPR‐Cas9 system enables the rapid generation of animal models, including mouse, which can precis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…AMOTs, in particular, AMOTL1, are involved in regulation of organogenesis. Similar to the family reported by Liegel et al (2019), the individual described herein harbors a heterozygous missense variant in AMOTL1 that is predicted to alter a highly conserved site. The proband suffered from oro-palatine and earlobe maldevelopment.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…AMOTs, in particular, AMOTL1, are involved in regulation of organogenesis. Similar to the family reported by Liegel et al (2019), the individual described herein harbors a heterozygous missense variant in AMOTL1 that is predicted to alter a highly conserved site. The proband suffered from oro-palatine and earlobe maldevelopment.…”
Section: Discussionsupporting
confidence: 54%
“…Notably, the missense variant reported in Liegel et al (2019) affects a residue only three amino acids away from that described here (p. (Arg157Cys) and p.(Pro160Leu), respectively), suggesting that there may be an important functional domain in this region. Although studies in mice with a missense Arg157Cys AMOTL1 variant were shown to result in increased embryonal death rates in both heterozygous and homozygous forms, none of the phenotypic features seen in humans with similar mutations were observed.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In fact, it is now accepted that the previous thresholds for calling a variant rare (and therefore potentially deleterious) were too lenient and may account for many published false associations between variants and human disease (Lek et al, 2016). In the absence of independent cases, detailed functional studies in model systems are essential for providing the evidence of causality (Liegel et al, 2019;Lukacs et al, 2019).…”
Section: Introductionmentioning
confidence: 99%